Exploring the causes and consequences of income inequality in India - Akshita Sheoran (Innovative Research Thoughts, 2024)
The unequal income distribution among people or households within a society is called income inequality. It is a crucial socioeconomic problem that has an impact on the foundation of all countries. With its wide diversity and intricate social structure, India is a country where economic inequality poses special difficulties and ramifications. This essay investigates the origins and effects of income disparity in India, looking at its historical development, relevance, and the urgent need for in-depth study in this area. The degree to which income is dispersed unevenly among a population is known as income inequality. Numerous income distribution ratios, the Lorenz curve, and the Gini coefficient are among the statistical methods frequently used to measure this inequality. Greater inequality is indicated by a higher Gini coefficient, and more equitable income distribution is shown by a lower coefficient. Income inequality can take many different forms in India, such as regional differences, urban-rural splits, and socioeconomic stratifications.